An understanding in the consumers perceptions of interacting with market affiliates of the parent brand USN in South Africa. - Rees, Justin (The IIE, 2022)
This study will be valuable as it intends to contribute to the global body of knowledge as well as provide crucial consumer insight onto the existing market affiliation programs of the brand Ultimate Sports Nutrition (USN). This field of research is needed to be explored as there are currently no published research papers analysing the consumer perceptions of South Africa in relation to the concept market affiliation. Market affiliation as a concept will be provided within the literature review of this proposal. Market affiliation is a relatively recent marketing strategy utilised by brands and businesses world-wide. Market affiliation is the concept whereby a brand or organisation would allow an external independent individual or ‘influencer’ to assist in increasing a company’s product or service sales. For example, let us use the brand USN, USN market affiliation would entail the brand to acquire the ‘ideal’ consumer and use them to influence others like -minded to the individual with incentive by commission for each sale referenced by the consumer. Affiliate marketers generally do not store or hold onto stock, a brand may send some products to the affiliate so that the affiliate can create digital content with the products. So, since USN is a health and fitness brand that specialises in hard-core exercise and workout supplements. USN would then sign with a frequent gym member (For example’s sake the gym member will be referred to as the affiliate) who matches with the identity of the brand, and that specific affiliate would then be given a code or a personal unique website address to disseminate amongst their personal networks. Each time someone from the personal networks clicks or taps on that affiliate’s specific link, USN would have tracked that and if the consumer from the personal network purchases a product, the affiliate then earns their commission from that online interaction. The realm of market affiliates is mainly restricted to the online platforms for tracking reasons. 6 Current research in the topic of market affiliation showcases that most forms of marketing affiliation strategies are successful, however, none of that of claim can be proven within the South African context. By conducting this research, the social relations within the South African climate of marketing affiliation and the consumers can be better seen and understood. This research is interesting as the results cannot be pre-determined and the research will either prove or disprove current research on the topic. This researcher believes that the world is created through social construct and social interaction, thereby this research would entail gaining the social understanding of market affiliation from consumers who have interacted with affiliates in South Africa.
Keywords: Market affiliation; Branding; Brand equity; Network marketing; Influencer marketing; Brand reputation